Sasaknese Cultural Identity Embedded in Zainuddin Abdul Madjid International Airport Design - Yune Andryani Pinem; Muhamad Pua Pandi; Kartika Fajar Nieamah; Nanik Rianandita Sari (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study investigates the integration of Sasaknese cultural elements into the architecture and interior design of Zainuddin Abdul Madjid International Airport (ZAMIA) in Lombok, Indonesia. Adopting a qualitative approach grounded in ethnolinguistics and cultural pragmatics, it analyzes how identity and social values are expressed through spatial forms, symbols, visual design, and naming practices. Data were collected through site observations, architectural analysis, and interviews with airport personnel and Sasaknese cultural elder “Jerokeliang”. The findings reveal that ZAMIA incorporates symbolic elements such as bale roof structures, weaving motifs, and pictures that introduce visitors to Sasak traditions. While airport officials frame these features as part of tourism and cultural promotion, elder emphasizes their partial representation of a broader heritage. The preservation of original Sasak terms for cultural items further supports language maintenance and the transmission of oral traditions. Although not all cultural dimensions are fully represented, the airport successfully fosters a culturally resonant environment. This study demonstrates how public infrastructure can function as a platform for cultural preservation and community-based tourism through embedded local identity.